Secondary traumatic stress, burnout, compassion satisfaction, and perceived organizational trauma readiness in forensic science professionals - Levin, Andrew P.; Putney, Heidi; Crimmins, Danielle; McGrath, Jonathan G. (Journal of forensic sciences, 2021)
Secondary traumatic stress, burnout, and compassion satisfaction have been described since the 1980s and extensively studied in first responders, law enforcement, legal professionals, and human service providers. There are few studies in forensic science professionals. To determine levels of secondary traumatic stress, burnout, and compassion satisfaction and relate these to demographics and job characteristics, we administered online a modified version of the Professional Quality of Life (ProQOL) questionnaire to professionals in crime laboratories and medical examiner offices. Participants also completed a modified version of the Vicarious Trauma‐Organizational Readiness Guide (VT‐ORG) to measure perceptions of their organizations’ efforts to address vicarious trauma and promote health and wellness. Results from 419 subjects indicated that field‐based forensic science professionals registered higher levels of secondary traumatic stress compared to laboratory‐based professionals, but burnout and compassion satisfaction were not significantly different between these groups. Demographic variables did not predict any of these outcome measures, but work with victims’ families and testifying significantly, albeit weakly, predicted higher secondary traumatic stress. Greater employee belief that their organizations were addressing issues of stress and trauma predicted lower levels of secondary traumatic stress and burnout and higher levels of compassion satisfaction. Write‐in responses by participants paralleled the quantitative findings. These results indicate a need to strengthen organizational efforts to address stress and trauma and promote health and wellness, particularly in professionals with direct field‐based exposure to crime scenes, contact with victims’ families, and responsibility for testifying.